HUBUNGAN INDEKS LUAS DAUN TERHADAP EFEKTIVITAS FOTOSINTSIS - Oktafian Sihaloho; Sinaga , Ferdi; Beriasi Fransisko Sinaga; Ihsan Taulani; Diky Anggara; Hari Gunawan (Fakultas Pertanian Universitas Janabadra, 2026)
Leaf Area Index (LAI) is a key biophysical indicator that reflects canopy structure and its capacity to intercept solar radiation, thereby influencing photosynthetic performance. This study aims to examine the relationship between Leaf Area Index and photosynthetic effectiveness in plants. A quantitative observational approach was employed by measuring leaf area, plant density, and photosynthetic rate using standard plant physiological methods. The results indicate that an increase in LAI generally enhances photosynthetic effectiveness due to improved light interception and greater chlorophyll availability. However, excessively high LAI leads to self-shading within the canopy, reducing light penetration to lower leaves and ultimately decreasing photosynthetic efficiency. These findings demonstrate that the relationship between LAI and photosynthetic effectiveness is non-linear and characterized by an optimal LAI range that maximizes photosynthetic performance. Understanding this relationship is crucial for optimizing crop management strategies, improving canopy architecture, and increasing plant productivity in a sustainable manner.